PENGARUH INVESTASI, TENAGA KERJA, DAN PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI PROPINSI SULAWESI SELATAN - Andi Wahana (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2020)
The purpose of this study is to determine and analyze the effect of the realization of the value of Foreign Investment (PMA) on economic growth in South Sulawesi Province, to determine and analyze the realization of the value of Domestic Investment (PMDN) on economic growth in South Sulawesi Province, to determine and analyze the influence of economic growth in South Sulawesi Province, and to determine and analyze government spending on economic growth in South Sulawesi Province. The analytical tool used in this research is linear regression analysis with a quantitative model. The results of the study indicate that investment through PMA and PMDN has a positive and significant effect on economic growth in South Sulawesi Province, employment has a positive and significant effect on economic growth in South Sulawesi Province, government spending has a positive and significant effect on economic growth in South Sulawesi Province